Premature birth and the new coronavirus: An integrative review (Research, Society and Development, 2021)
The main objective of this integrative review was to identify scientific evidence present in publications on the relationship between premature birth and Covid-19. As a secondary objective, to verify other clinical outcomes present in the pregnant women included in this review. Selection criteria and controlled descriptors were used to search for articles indexed in the Medline / Pubmed and Lilacs databases in April 2021. The final selection consisted of 23 articles. Studies show that premature birth and fetal distress are possible complications of pregnancy in women with Covid-19, high rates of cesarean delivery were also observed in this population. It is concluded that Covid-19 in pregnant women has important impacts on perinatal and neonatal outcomes. The results mentioned in the studies may provide additional guidance to improve prenatal counseling for patients with Covid-19 infection during pregnancy.